A Cell‐Free Silk Fibroin Biomaterial Strategy Promotes In Situ Cartilage Regeneration Via Programmed Releases of Bioactive Molecules. Issue 1 (7th November 2022) - Mao, Zhinan; Bi, Xuewei; Wu, Chengai; Zheng, Yufeng; Shu, Xiong; Wu, Sujun; Guan, Juan; Ritchie, Robert O.
Abstract: In situ tissue regeneration using cell‐free biofunctional scaffolds has been extensively studied as a promising alternative strategy to promote cartilage repair. In this study, a cartilage‐biomimetic silk fibroin (SF)‐based scaffold with controlled sequential release of two bioactive molecules is developed. Transforming growth factor‐ β 1 (TGF‐ β 1) is initially loaded onto the SF scaffolds by physical absorption, which are then successively functionalized with bone marrow mesenchymal stem cells (BMSCs)‐specific‐affinity peptide (E7) via gradient degradation coating of Silk fibroin Methacryloyl (SilMA)/Hyaluronic acid Methacryloyl (HAMA). Such SF‐based scaffolds exhibit excellent structural stability and catilage‐like mechanical properties, thus providing a desirable 3D microenvironment for cartilage reconstruction. Furthermore, rapid initial release of E7 during the first few days, followed by slow and sustained release of TGF‐ β 1 for as long as few weeks, synergistically induced the recruitment of BMSCs and chondrogenic differentiation of them in vitro. Finally, in vivo studies indicate that the implantation of the biofunctional scaffold markedly promote in situ cartilage regeneration in a rabbit cartilage defect model. It is believed that this cartilage‐biomimetic biofunctional SF‐based scaffold with sequential controlled release of E7 and TGF‐ β 1 may have a promising potential for improved cartilage tissue engineering. Abstract : A biofunctional scaffold is constructed that can effectively and specifically recruit endogenous stem cells to the site of injury, and improve the local chondrogenic microenvironment. Importantly, the dual‐drug release pattern is designed to match the physiological process of cartilage regeneration. The strategy stimulates the body's own regenerative potential to achieve in situ articular cartilage regeneration.